Cancer Epidemiology (Turkey Health Literacy Journal, 2022)
Cancer is a term used for a large group of diseases that result from the transformation of normal cells into tumor cells. After cardiovascular diseases, cancer is the second leading cause of death from noncommunicable diseases. Vulnerable and socially disadvantaged people get cancer and die at an earlier age. In our country, cancer is registered with the Population-Based Active Cancer Registry System. Although the incidence of cancer in our country is higher in men than in the world, it is similar in women. In our country, lung cancer is the most common in men, and breast cancer is the first in women. Colorectal cancers are in the third place in men and women. 47.9% of breast cancers in women, 55.2% of cervical cancers, and 34.1% of colorectal cancers in women and men are localized at the time of diagnosis. Free breast, colorectal and cervical cancer screenings in our country have a great contribution to the detection of these cancers at the localized stage. 56.5% of lung cancer is diagnosed when there is distant metastasis. The etiology of 90-95% of all cancer cases is based on the environment and lifestyle. Between 30 and 50% of cancers can be prevented, primarily by not using tobacco products, maintaining a healthy body weight, eating a healthy diet, including fruits and vegetables, exercising regularly, avoiding alcohol and other risk factors, and implementing evidence-based prevention strategies. Many cancers have a good chance of recovery if they are detected early and treated appropriately.